Selection of DNA aptamers against Cancer-Targeting Murine Antibodies - Nisbet, Laura Jade (Rhodes University, Faculty of Science, Biotechnology Innovation Centre)
Access restricted. Access embargoed until 2025.
Keywords: Uncatalogued